Winning - Jack; Welch; Welch, Suzy (New York Harper Collins Publishers, 2005)
During his forty-year career at General Electric, Welch led the company to year-after-year success around the globe, in multiple markets, against brutal competition. His honest, be-the-best style of management became the gold standard in business, with his relentless focus on people, teamwork, and profits. Since Welch retired in 2001 as chairman and CEO of General Electric, he has traveled the world, speaking and answering questions. Now, he has written both a philosophical and pragmatic book, which lays out his answers. He begins with his business philosophy, exploring the importance of values, candor, differentiation, and voice and dignity for all. The core of the book looks inside the company, from leadership to picking winners to making change happen; outside, at the competition; and at managing your career--from finding the right job to achieving work-life balance.
Age Group: Adult
Underneath it all. Mission and values : so much hot air about something so real ; Candor : the biggest dirty little secret in business ; Differentiation : cruel and Darwinian? Try fair and effective ; Voice and dignity : every brain in the game. -- Your company. Leadership : it's not just about you ; Hiring : what winners are made of ; People management : you've got the right players, now what? ; Parting ways : letting go is hard to do ; Change : mountains do move ; Crisis management : from oh-God-no to yes-we're-fine. -- Your competition. Strategy : it's all in the sauce ; Budgeting : reinventing the ritual ; Organic growth : so you want to start something new ; Mergers and acquisitions : deal heat and other deadly sins ; Six sigma : better than a trip to the dentist. -- Your career. The right job : find it and you'll never really work again ; Getting promoted : sorry, no shortcuts ; Hard spots : that damn boss ; Work-life balance ; everything you always wanted to know about having it all (but were afraid to hear). -- Tying up loose ends. Here, there, and everywhere : the questions that almost got away.
Includes index.
Keywords: Negotiation in business; Strategic planning; Success in business